2021
DOI: 10.1155/2021/2060288
|View full text |Cite
|
Sign up to set email alerts
|

Phototoxicity of Ultraviolet‐A against the Whitefly Bemisia tabaci and Its Compatibility with an Entomopathogenic Fungus and Whitefly Parasitoid

Abstract: Ultraviolet (UV) radiation significantly affects insect life and, as a result, has been widely used to control different invertebrate pests. The current results demonstrate that when Bemisia tabaci first instar nymphs are exposed to UV-A light for 12, 24, 48, and 72 h, their developmental and biological parameters are negatively affected by UV-A exposure; the effect increased with an increase in exposure time. We hypothesized that UV-A light is compatible with other biological control agents. Results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 81 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…The current study reported that exposure to UV-C radiation reduces the immunity of P. xylostella, which increase the effectiveness of C. fumosorosea . Khan et al [ 7 ] also reported that if Bemisia tabaci was exposed to UV-A before application of C. fumosorosea , the LC 50 decreases with an increase in exposure time, which implies that the B. tabaci become less and less immune against fungal infection due to UV-A exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study reported that exposure to UV-C radiation reduces the immunity of P. xylostella, which increase the effectiveness of C. fumosorosea . Khan et al [ 7 ] also reported that if Bemisia tabaci was exposed to UV-A before application of C. fumosorosea , the LC 50 decreases with an increase in exposure time, which implies that the B. tabaci become less and less immune against fungal infection due to UV-A exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Most moths can tolerate UV irradiation; however, blacklight, a synthetic form of UV-light, has been extensively used to control nocturnal moths [ 3 , 4 ]. Previous studies reported a direct effect of UV light on insect behavior [ 5 ], development, biology, and physiology [ 6 , 7 ], and biochemistry [ 8 ], but there is no study available reporting direct mortality of moths caused by UV light.…”
Section: Introductionmentioning
confidence: 99%
“…Natural enemies (predators, parasitoids, and entomophagous fungi) of B. tabaci have been thoroughly investigated and reviewed [104,105,220,221]. Over the last 20 years, enormous studies have proven the efficacy of parasitoids, entomopathogenic organisms, and predators in managing destructive insect pests including whiteflies on different agricultural plants [13,[222][223][224].…”
Section: Biological Strategiesmentioning
confidence: 99%
“…6,16,17 However, regarding the latter, numerous environmental stresses such as ozone depletion, increased UV radiation, biodiversity destruction, and temperature may impact EPF normal development in the field, whether the EPF have been applied as part of IPM plans or they are naturally present in these habitats. 18,19 One of the most harmful environmental factors affecting the depletion of EPF propagules is the sunlight fraction UV-B radiation (⊗ of 280-315 nm), which could directly affect the presence and persistence of EPF conidia in epigeal habitats. 7,20 It is welldocumented that UV-B radiation acts directly on DNA, RNA, and intracellular macromolecules (proteins, ribosomes, and biomembranes), and the development of compounds such as the reactive oxygen species (ROS) resulting in genetic modifications, cell toxicity, and signal pathway modification.…”
Section: Introductionmentioning
confidence: 99%